Efficacy of a plant growth regulator in the culture of coffee =Eficácia de biorregulador na cultura do café (Bioscience Journal, 2016)
The purpose of this work was to evaluate the efficacy of a plant growth regulator applied at different growth stages in coffee. The experiment was conducted in the years 2010/2011 and 2011/2012 on the Docas 1 farm, using Mundo Novo IAC 379-19 coffee cultivar, with spacing 4 meter between rows and 0.8 meter between plants and 10 plants per plot. The experimental design was in blocks at random, with two factors and three repetitions. The first factor was the dose of the product (0.25 and 0.5 liter per hectare per application) and second factor was the time of applications according to the phenological stages (pre-flowering, post-flowering and pinhead). The control treatment (control) consisted of the absence of the application of the plant growth regulator. Biometric aspects (number of internodes and length of reproductive branches in centimeters, number of fruits on the fourth and fifth node on reproductive branches) and productivity were evaluated. Collected data were analyzed using Tukey test at 0.05 of significance. The application of a plant growth regulator at different growth stages of development of coffee leads to increased biometric variables in coffee: the number of internodes, the average number of fruits on the fourth and fifth node and the length of reproductive branches. The productivity of coffee can be increased with the use of plant growth regulators, particularly at the dose of 0.5 liter per hectare per application, regardless of the application period, promoting productivity up to 46.9%. It is not possible to state that the presence of substances similar to phytohormones in plant growth regulators is responsible for the increase in productivity without making isolate application of these substances.